Cover Image, Volume 27, Issue 4. Issue 4 (20th March 2017) - Barbeau, Emmanuel J.; Chauvel, Patrick; Moulin, Christopher J.A.; Regis, Jean; Liégeois‐Chauvel, Catherine
Abstract : This cover image, by Emmanuel J. Barbeau et al., is based on the Research Article Hippocampus duality: Memory and novelty detection are subserved by distinct mechanisms, DOI: 10.1002/hipo.22699 .